2011
DOI: 10.1007/s10059-011-0137-0
|View full text |Cite
|
Sign up to set email alerts
|

Jolkinolide B from Euphorbia fischeriana Steud Induces Apoptosis in Human Leukemic U937 Cells through PI3K/Akt and XIAP Pathways

Abstract: Jolkinolide B, a bioactive diterpene isolated from the roots of Euphorbia fischeriana Steud, is known to induce apoptosis in cancer cells. However, the molecular mechanism of its anti-cancer activity has not been fully elucidated. In the present study, we found that Jolkinolide B reduced cell viability and induced apoptosis in a dose-and timedependent manner in human leukemic U937. The induction of apoptosis was also accompanied by the downregulation of PI3K/Akt and the inhibitor of apoptosis protein (IAP) fam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 25 publications
0
31
1
Order By: Relevance
“…JB is a diterpenoid component isolated from the dried roots of Euphorbia fischeriana Steud . It has been reported that JB regulates proliferation and induces apoptosis in human leukemic U937 cell7. Another document evaluates the anti-metastatic role and mechanisms of JB on breast cancer MDA-MB-231 cells by the integrin/FAK and ERK pathways in vitro 8.…”
mentioning
confidence: 99%
“…JB is a diterpenoid component isolated from the dried roots of Euphorbia fischeriana Steud . It has been reported that JB regulates proliferation and induces apoptosis in human leukemic U937 cell7. Another document evaluates the anti-metastatic role and mechanisms of JB on breast cancer MDA-MB-231 cells by the integrin/FAK and ERK pathways in vitro 8.…”
mentioning
confidence: 99%
“…An increasing number of studies indicate that diterpenoids from E. fischeriana Steud, such as 17-hydroxy-jolkinolide B, 17-acetoxyjolkinolide B and jolkinolide B, are able to induce apoptosis in tumor cells, including human leukemic U937, MDA-MB-231 and HepG2 cells, by modulating the IκB kinase, signal transducer and activator of transcription, or phosphoinositide 3-kinase/Akt pathways (10,20,21). Several studies have also suggested that diterpenoid compounds are able to inhibit cell-ECM adhesion (13,22).…”
Section: Discussionmentioning
confidence: 99%
“…Jolkinolide B is a biologically active chemical isolated from Euphorbia fischeriana Steud. Previous studies have revealed that this chemical acts as an anticancer agent (10,11). However, it is not clear whether jolkinolide B exerts anti-metastasis effects by suppressing the expression of adhesion molecules, such as β 1 -integrin.…”
Section: Introductionmentioning
confidence: 99%
“…The cytotoxicity of all 13 compounds was tested by MTT method (Wang et al 2009(Wang et al , 2011. The result showed that compounds 1 and 2 had an intensive effect with IC 50 levels of 23.…”
Section: Cytotoxicitymentioning
confidence: 99%